2019
DOI: 10.1155/2019/2519205
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Dental Metal Implants: Impact on Human Health (Metal as a Risk Factor of Implantologic Treatment)

Abstract: Dental implants are often made of titanium alloys. Implant therapy currently promises a good long-term result without impacting health; however, its success depends on many factors. In this article, the authors focus on the most common risk factors associated with metallic surgical implants. Titanium-induced hypersensitivity can lead to symptoms of implant rejection. Corrosion and biofilm formation are additional situations in which these symptoms may occur. For medical purposes, it is important to define and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…However, the metallic color of the titanium implant or abutment is visible through the soft peri-implant tissue, and this results in an unpleasant aesthetic outcome [ 7 ]. The long-term existence of metal materials in humid oral environments can easily lead to chemical corrosion [ 8 ]; additionally, patients with metallic allergies will have a greater risk of developing allergic reactions to metals or alloy materials [ 9 ]. Therefore, in the past decade, the choice of materials for dental implants or abutment has gradually shifted to aesthetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the metallic color of the titanium implant or abutment is visible through the soft peri-implant tissue, and this results in an unpleasant aesthetic outcome [ 7 ]. The long-term existence of metal materials in humid oral environments can easily lead to chemical corrosion [ 8 ]; additionally, patients with metallic allergies will have a greater risk of developing allergic reactions to metals or alloy materials [ 9 ]. Therefore, in the past decade, the choice of materials for dental implants or abutment has gradually shifted to aesthetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term biological requirements, especially biocompatibility and resistance to bacterial contamination, may be problematic. Titanium is considered to be the most biocompatible material thanks to its high corrosion resistance [7][8][9]. On the other hand, it has been reported that its particles may diffuse to the surrounding tissues causing allergic reactions, cytotoxicity, or pro-inflammatory responses [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium is considered to be the most biocompatible material thanks to its high corrosion resistance [7][8][9]. On the other hand, it has been reported that its particles may diffuse to the surrounding tissues causing allergic reactions, cytotoxicity, or pro-inflammatory responses [7][8][9][10][11][12][13][14]. Therefore, studies involving titanium alloys must be conducted with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…These metals are bioinert but in some cases they induce immunological responses, including allergies. Another disadvantage is that they are not biodegradable [93,94].…”
Section: Biomaterialsmentioning
confidence: 99%